Strategically Formulating Aggregation‐Induced Emission‐Active Phosphorescent Emitters by Restricting the Coordination Skeletal Deformation of Pt(II) Complexes Containing Two Independent Monodentate Ligands. Issue 13 (10th May 2020) - Yang, Xiaolong; Yue, Ling; Yu, Yue; Liu, Boao; Dang, Jingshuang; Sun, Yuanhui; Zhou, Guijiang; Wu, Zhaoxin; Wong, Wai‐Yeung
Abstract: Aggregation‐induced emission (AIE)‐active phosphorescent emitters have intrinsic advantages in time‐gated imaging/sensing and improving the electroluminescent efficiencies of organic light‐emitting devices (OLEDs). However, compared with the very prosperous and fruitful developments of AIE‐active fluorescent emitters and related working mechanisms, the progresses on AIE‐active phosphorescent emitters and associated AIE mechanisms are still relatively slow. Herein, the AIE properties of a series of phosphorescent Pt(II) complexes with two monodentate ligands are reported. Compared with the conventional rigid Pt(II) complexes bearing two bidentate ligands or one tri‐/tetradentate ligand, the incorporation of two monodentate ligands provides the resulting Pt(II) complexes with more room to deform their coordination skeletons from the square‐planar geometry in the ground state to the quasi‐tetrahedral configuration in the excited state, causing poor solution emissions. In doped films and aggregate states, intense emissions are observed for these Pt(II) complexes. The as‐fabricated solution‐processed OLED exhibits an impressively high external quantum efficiency of 21.7%. This study provides an effective way to develop excellent AIE‐active phosphorescent emitters. Abstract : Efficient aggregation‐induced emission (AIE)‐active Pt(II) complexes containing two independent monodentate ligands are developed based on a new working mechanism, namely, restriction of coordination skeletal deformation. A solution‐processed organic light‐emitting device (OLED) based on the AIE‐active Pt(II) complex displays an outstanding performance with the peak EQE of 21.7%, ranking it among the best AIE‐active phosphorescent emitters for OLEDs.